2011
DOI: 10.1007/s11760-011-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

User authentication based on foot motion

Abstract: In nearly all current systems, user authentication mechanism is one time and static. Although such type of user authentication is sufficient for many types of applications, in some scenarios, continuous or periodic re-verification of the identity is desirable, especially in high-security application. In this paper, we study user authentication based on 3D foot motion, which can be suitable for periodic identity re-verification purposes. Three-directional (3D) motion of the foot (in terms of acceleration signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…As it was shown in Fig. 4, we manually 7 the cycle borders at the cyclic valley points of the gait acceleration series recorded at the ankle. 8 Normally, 7-14 full step cycles (one left and one right step constitute a full step) existed within the useful segment of a record.…”
Section: Zju-gaitacc Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…As it was shown in Fig. 4, we manually 7 the cycle borders at the cyclic valley points of the gait acceleration series recorded at the ankle. 8 Normally, 7-14 full step cycles (one left and one right step constitute a full step) existed within the useful segment of a record.…”
Section: Zju-gaitacc Datasetmentioning
confidence: 99%
“…A participant might also dress in different ways for the two sessions. What is more, as we did not use particularly designed clothes or shoes for acceleration acquisition (they are used in some existing pieces of works, see [7]), the Wii remotes could not be mounted on the specific body locations very precisely for different participants and sessions. It imitated the practical scenarios of wearable and portable devices.…”
Section: Zju-gaitacc Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…It was Cutting and Kozlowski [2] who already conducted researches which demonstrated that a human has a skill of recognizing the people he knows from a long distance by their way of moving, even if they wear clothes different than usual and have changed their hairstyle. Gafurov [4] In case of video based methods the picture registered is usually converted frame by frame into silhouette sequences. Subsequently, depending on the applied methods there occurs an attempt at reading of selected parameter's of the human's gait and classification of a person [1], [6].…”
Section: Introductionmentioning
confidence: 99%